Pemberdayaan Kelompok Tani pada Teknologi Pemanfaatan Energi Baru Terbarukan Berbasis Jarak Pagar untuk Percepatan Terbentuknya Desa Mandiri Energi di Kawasan Amor-Amor, Kabupaten Lombok Utara, NTB - Bambang Budi Santoso; I Wayan Suadnya; I Gst. Pt. Muliarta Aryana; I Komang Damar Jaya (Jurnal Gema Ngabdi, 2019)
JJatropha curcas L. in the Amor-Amor, North Lombok, West Nusa Tenggara have been grown and developed long ago. It was just as fences of land, yards, and roads, and used as a source of traditional medicine but not as alternative energy sources and as a crop yield. Even if Jatropha seed oil can be used as an energy source family. No commercialize and intensively cultivation, such as the use of high yielding varieties, planting distance, fertilizing and other maintenance, and intercropping with food crops. Another problem faced by farmer groups members is difficult to get fertilizers, proper cultivation techniques, the difficulty of obtaining diesel fuel to operate the water bore-pumps for irrigation purposes. Through science and technology communication activities (Ipteks) was expected to formed the Energy Independent Village. This Ipteks such as counselling, training, and demonstrations conducted by the research team has been able to provide rationalization and true understanding to the farmer groups on aspects of Jatropha as an alternative source of fuel.  Understanding includes benefits of crop as a source of fuel, good cultivation techniques, the potential economic and environmental impact, plant waste management and Jatropha seed oil processing and other benefits plant. Counselling and training undertaken has been able to generate interest and need for farmers to adopt the technology introduced. In addition, education and training was provided to farmers has also empowered them, by involving farmer participatory on any activities performed. Farmer’s empowerment has successes. It was at the phase awareness, interest, and evaluation of the adoption process.